Penggunaan Sistem Informasi Akuntansi Pada Pelaporan Keuangan Organisasi: Studi Kasus Pada Non-Governmental Organization - Luluk Ayuning Tyas; Windra Laksana Putra (Lembaga Pengembangan Kinerja Dosen, 2023)
Advances in technology have made Accounting Information Systems an inseparable part of all forms of organization. Organizations use standardized systems to ensure a balance of comparison and reporting. The application of the Accounting Information System (SIA) in non-governmental organizations has not been carried out optimally due to several obstacles. This study seeks to explore the use of accounting information systems used by non-governmental organizations in the Central Java region and to determine whether these organizations are capable of designing systems independently in accordance with international standards. The study also evaluates system usage, user competence, system quality, design capabilities and their impact on financial reporting. The research method used surveys and interviews of 50 employees of non-governmental organizations who had used accounting information systems. Quantitative data processing using the SPSS program and thematic analysis for interview results. The findings of this study show that there is a positive and significant relationship between the Accounting Confirmation System and financial reporting. The findings show that there is a positive and significant relationship between AIS and financial reporting. However, it was also found that not all were able to design the SIA independently due to a shortage of experts and funding.